Lead discovery of a guanidinyl tryptophan derivative on amyloid cascade inhibition - Piyapan Suwanttananuruk (2020)
© 2020 Piyapan Suwanttananuruk et al., published by De Gruyter 2020. Amyloid cascade, one of pathogenic pathways of Alzheimer's disease (AD), was focused as one of drug discovery targets. In this study, β-secretase (BACE1) inhibitors were designed aiming at the development of multifunctional compounds targeting amyloid pathogenic cascade. Tryptophan was used as a core structure due to its properties of the central nervous system (CNS) penetration and BACE1 inhibition activity. Three amino acid residues and guanidine were selected as linkers to connect the tryptophan core structure and the extended aromatic moieties. The distance between the aromatic systems of the core structure and the extended moieties was kept at the optimal length for amyloid-β (Aβ) peptide binding to inhibit its fibrillation and aggregation. Sixteen designed compounds were evaluated in silico. Eight hit compounds of TSR and TGN series containing serine and guanidine linkers, respectively, were identified and synthesized based on docking results. TSR2 and TGN2 were found to exert strong actions as BACE1 (IC50 24.18 μM and 22.35 μM) and amyloid aggregation inhibitors (IC50 37.06 μM and 36.12 μM). Only TGN2 demonstrated a neuroprotective effect in SH-SY5Y cells by significantly reducing Aβ-induced cell death at a concentration of 2.62 μM. These results support the validity of multifunctional approaches to inhibition of the β-amyloid cascade.